Creating Social Justice: A Conversation with Julia Álvarez - Rebeca Moreno-Orama; Julia Álvarez (Latin American Literary Review, 2017)
In this interview, Julia Álvarez shares her insights on the power of storytelling to overturn political injustices, such as the one suffered by the Dominican people, and in particular by the Mirabal sisters, under General Rafael Trujillo’s thirty–one years of dictatorship. The writer also offers a compelling vision of community engagement through the creation of a literary space in which issues affecting the Latino population in the United States can be explored. Álvarez reveals the importance of the imagination in envisioning a distinct narrative space where the effects of NAFTA on undocumented Mexican farmer workers or the challenges faced by the children of undocumented immigrants are brought to life through the singularity of her characters. She particularly stresses her commitment to creating a multiplicity of voices and approaches in order to provoke an independent but well-rounded discussion of the conflicting perspectives on these issues.